An on-site teaching laboratory in a village damaged by the 2009 Abruzzo earthquake (Fracture and Structural Integrity, 2018)
This paper illustrates a two-year program of summer internships that involved forty students from the School of Engineering (University of Pisa) in 2010-2011. The activity consisted in a systematic survey of damages occurred in a village after the 2009 Abruzzo earthquake and in the preparation of documents addressed to a reconstruction plan. The historical center of San Pio delle Camere (1000 inhabitants) was fully surveyed, including about 140 hypogeal sites. Each student spent at least one month in these activities, funded by study grants provided by the Tuscany Region. Teams of two-three students performed well-defined work packages, led by a tutor, who established roles and functions. The students discussed the progress made preparing a weekly report. Moreover, preliminary structural analyses were carried out to assess the seismic vulnerability of some relevant buildings, fully available to the students. The main results were published in a book presented in a workshop. Most of the results were used to set up the official reconstruction plan of the village. During this on-site laboratory, the students could experience the effects of that destructive earthquake on the population, visiting also the damaged surrounding towns and seeing with their own eyes many cases of structural collapses.
Keywords: Internships; Abruzzo earthquake; teaching laboratory; educational activity; structural analysis; survey of damages